Return to the U.N. : UN diplomacy in regional conflicts - Berridge, Geoff (Basingstoke : Macmillan, 1991)
1987 onwards has seen an unprecedented return of countries to the United Nations. This book examines some of the reasons why. It assesses the effects of changes at the UN headquarters, as well as the recent history of UN diplomacy. Berridge has also written "Diplomacy at the UN".
Includes index.
Includes bibliographical references and index.
Keywords: United Nations; United Nations; United Nations; Vereinte Nationen; Pacific settlement of international disputes; 89.72 international organizations; Pacific settlement of international disputes; armed conflict; Security Council; UN Resolution; regional level; role of USA; role of USSR; United Nations; International cooperation